Severe Elephant Endotheliotropic Herpesvirus 6 Associated Disease in Two African Elephants Under Human Care in Austria - Stella Knüppel; Folko Balfanz; Christiane Riedel; Verena Strauss; Tabitha E. Hoornweg; Katharina Dimmel; Karin Walk; Anna Kübber-Heiss; Annika Posautz; Thomas Voracek; Azza Abdelgawad; Jakob Trimpert; et al. (Animals)
In 2021, a captive two-year-old African elephant died of cardiovascular failure in Austria. Lesions were indicative of elephant endotheliotropic herpesvirus (EEHV) associated disease, and the presence of EEHV6 could be detected by PCR. About two months later, an eight-year-old female elephant from the same herd showed typical clinical signs of EEHV-related hemorrhagic disease, which coincided with EEHV6 viremia. The animal underwent anti-herpesviral therapy and recovered quickly. Subsequently, blood and trunk wash samples from all elephants of the herd were monitored weekly for the presence of EEHV6-specific nucleic acids by qPCR. A retrospective analysis of the samples revealed repeated EEHV6 reactivation and the presence of EEHV3 in the samples of one animal. Our findings underline the threat EEHV6 poses to juvenile African elephants and emphasize the need for regular monitoring of viremia and virus excretion to prevent fatalities and predict transmission events.